(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
This study explores the philosophical conceptions of the world, human life, and society in Theravada and Vajrayana Buddhism, focusing on their interpretations and social expressions within Nepal. Drawing on canonical sources such as the Majjhima Nikaya, particularly the Balapaṇḍita Sutta, the research examines how moral causality is linked to social hierarchy—where sinful individuals are said to be reborn as Chaṇḍalas (outcastes), while the virtuous are reborn among higher castes. While such views are grounded in karmic ethics rather than birth-based essentialism, their social implications resonate within Nepal’s complex caste system. Theravada philosophy emphasizes impermanence (anicca), suffering (dukkha), and non-self (anatta), viewing time as cyclical and human life as a precious chance for liberation through ethical conduct and meditation. Vajrayana, by contrast, conceptualizes reality as empty (sunyata) and interdependent, offering transformative practices—including mantras, mandalas, and deity yoga—through which enlightenment can be achieved in a single lifetime. Time and worldly existence are seen as illusory yet useful for spiritual realization. This comparative study analyzes how both traditions interpret reality, time, karma, and social ethics. It investigates how these philosophical frameworks manifest in Nepal—where Theravada revivalist movements promote rationalist reform and egalitarianism, while Newar Vajrayana traditions integrate ritual, caste identity, and community life. Through textual analysis and contextual interpretation, the research highlights both convergence and divergence in their approaches, showing how Buddhist worldviews continue to shape moral values, social system, and spiritual aspirations in contemporary Nepal.